Enhancing communication in medical student placements: a quality improvement project on the use of WhatsApp for cardiothoracic placements - Raunaq Chaudhry (Future Healthcare Journal)
Introduction: Effective communication is essential in medical education to ensure smooth coordination and engagement during clinical placements. Traditional communication methods, such as emails, often lead to delayed responses and reduced student engagement. This quality improvement (QI) project assessed the efficacy of a WhatsApp group compared with traditional email communication among Imperial College medical students on 2-week cardiology placements. The primary aim was to improve response rates, student engagement and placement satisfaction. Materials and methods: A two-cycle plan–do–study–act (PDSA) methodology was utilised. In Cycle 1, baseline data were collected on email response times and student feedback regarding communication effectiveness. A WhatsApp group was then introduced as an intervention, with all students and relevant staff included. In Cycle 2, data collection focused on response times, engagement levels and placement satisfaction using WhatsApp logs and student feedback surveys. Quantitative analysis compared response time improvements, while qualitative feedback assessed student satisfaction. Results and discussion: Cycle 1 data indicated inconsistent and delayed email responses, with 60% of students reporting difficulties in receiving timely replies. Following the introduction of the WhatsApp group, Cycle 2 data showed a 75% reduction in response times, with a median response time improvement from 12 h (email) to under 1 h (WhatsApp). Student feedback indicated increased engagement and satisfaction, with 85% favouring WhatsApp over email for real-time communication. The integration of WhatsApp improved accessibility to supervisors and timely resolution of queries, demonstrating its effectiveness as a communication tool in medical placements. Conclusion: This QI project demonstrated that WhatsApp significantly enhances communication efficiency and student engagement in cardiology placements. Based on the positive outcomes, the WhatsApp group has been permanently integrated into the induction module for future education fellows. Further iterations will explore refining its use and expanding its application to other placements.